2014
DOI: 10.1007/s11356-014-3081-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential toxicity of amphenicol antibiotic: binding of chloramphenicol to human serum albumin

Abstract: Antibiotics are widely used in daily life but their abuse has posed a potential threat to human health. To evaluate the toxicity of chloramphenicol (CAP) at the protein level, the interaction between CAP and human serum albumin (HSA) was investigated by fluorescence, Ultraviolet-visible (UV-Vis) absorption, Fourier transform infrared (FT-IR) spectroscopy and molecular docking methods. Fluorescence data revealed that the fluorescence quenching of HSA by CAP was the result of the formation of CAP-HSA complex, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…With the health side-effects to humans and the emergence of drug-resistant bacteria (Chen et al, 2014), the use of these antibiotics was strictly limited in many countries including China, European Community, the United States, Canada and Japan. In China, CAP was prohibited for use in any food-producing animals and the maximum residue limit for TAP was set at 50 μg L −1 in milk.…”
Section: Introductionmentioning
confidence: 99%
“…With the health side-effects to humans and the emergence of drug-resistant bacteria (Chen et al, 2014), the use of these antibiotics was strictly limited in many countries including China, European Community, the United States, Canada and Japan. In China, CAP was prohibited for use in any food-producing animals and the maximum residue limit for TAP was set at 50 μg L −1 in milk.…”
Section: Introductionmentioning
confidence: 99%
“…40 To investigate the possible binding sites of MOXH, site marker displacement studies were conducted using phenylbutazone and ibuprofen as sites I and II probes, respectively. 41 The percentage of displacement (I) by a site marker can be calculated as follows: 15…”
Section: Site Marker Displacement Studiesmentioning
confidence: 99%
“…Chloramphenicol (CAP) was discovered in 1947, it is a highly efficient broad‐spectrum antibiotic, especially against Gram‐positive and Gram‐negative bacteria 1, 2 . However, many studies have shown that CAP administration produces many side effects in the human body, such as aplastic anaemia, leukaemia, grey infant syndrome, and so on 3, 4 . These results suggest that CAP residues in the food chain would cause food safety problems that could seriously harm human health 5–7 .…”
Section: Introductionmentioning
confidence: 99%